FIBRE OPTIC BRAGG STRUCTURES WITH MONOTONIC APODISATION CHARACTERISTICS - Klimek, Jacek (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2021)
The article discusses the principle of operation and the structure of chirped and uniform gratings. It presents the method of producing gratings with monotonic apodisation characteristics, and compares the spectral features of produced gratings with the those obtained by mathematical modelling.